2012
DOI: 10.3892/or.2012.2095
|View full text |Cite
|
Sign up to set email alerts
|

miR-27a regulates the self renewal of the H446 small cell lung cancer cell line in vitro

Abstract: Cancer growth is driven by cancer stem-like cells within a tumor, called cancer stem cells (CSCs). Since miRNAs can regulate cell-fate decisions, we compared miRNA expression in stem-like cells and differentiated cells from small cell lung cancer (SCLC) cell lines to develop further understanding of the molecular mechanisms involved in the pathogenesis of SCLC. First, SCLC stem-like cells were enriched by isolating sphere-forming cells using a defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Expression of miR-7 in metastatic breast CSCs was correlated with increased expression of the pluripotency gene KLF4, suggesting an important role for miRNA in CSC stemness and metastasis (117). In concordance with these studies, a pivotal role for microRNA in CSC maintenance has also been reported in models of colorectal, lung and hepatocellular carcinoma (118)(119)(120)(121). Moreover, a recent review provided evidence for a 30 miRNA signature correlating with expression in the TGFβ, Notch and Wnt signaling pathways, implicating their role in regulating EMT and CSCs (103).…”
Section: Role Of Micro Rna In Cerebral Metastasissupporting
confidence: 56%
“…Expression of miR-7 in metastatic breast CSCs was correlated with increased expression of the pluripotency gene KLF4, suggesting an important role for miRNA in CSC stemness and metastasis (117). In concordance with these studies, a pivotal role for microRNA in CSC maintenance has also been reported in models of colorectal, lung and hepatocellular carcinoma (118)(119)(120)(121). Moreover, a recent review provided evidence for a 30 miRNA signature correlating with expression in the TGFβ, Notch and Wnt signaling pathways, implicating their role in regulating EMT and CSCs (103).…”
Section: Role Of Micro Rna In Cerebral Metastasissupporting
confidence: 56%
“…Formerly, the important characteristics that determine the CSCs are self-renewal, and study has shown that miRNA regulates this important feature. Miao et al (116) discover that downregulation of miR-27 enhanced the properties of stem-like SCLC, whereby downregulation of miR-27 dedifferentiate non-tumorigenic cells into highly tumorigenic cells and was consistently downregulated in spheroid cells even at passage 4 (116). In addition, miR-27 was also reported to be downregulated in A549 cell that derived from NSCLC type (117).…”
Section: Therapeutic Strategies Of Lung Cscsmentioning
confidence: 99%
“…Furthermore, we identified two miRNAs, miR-27a, see also refs 52, 53, 54, and miR-33 that were downregulated following reprogramming exclusively in p53 wt cells (Figure 2c). …”
Section: Resultsmentioning
confidence: 82%